Substitution of the principles of balancing micro power systems with power deficit and consideration of consumer categories by using cyclic outage schedules - Kaplun, V.; Voytenko, V.; Remez, S. (Energy and Automation, 2026)
As a result of massive missile and drone attacks on the energy infrastructure, there is a power shortage in most regions of Ukraine, which causes emergency and stabilization outages. Under such conditions, it is important to effectively use the available energy potential to maintain the viability of regional energy systems, taking into account the power limit. The legislative and regulatory framework regulates the application of hourly and emergency outage schedules and power consumption restrictions, determining the priority of reliable power supply to critical infrastructure facilities. Connecting consumers of different priorities to common feeders of 6–10 kV consumer substations in real distribution networks significantly complicates dispatching management and requires substantiation of methods for optimizing power flow distribution under variable limits. The purpose of the study is to substantiate a mathematical model of power flow balancing taking into account the criticality of feeders based on cyclic outage schedules by using a mixed-integer model of power flow distribution in the three-level structure of the power island: transmission system operator - distribution system operator - feeders of consumer substations. The model determines the minimum duration of power supply of feeders depending on the load of consumers of the critical group, taking into account the power limit. Numerical modeling was performed for feeders of priority consumers with subsequent minimization of the total power moment as an indicator of flow distribution efficiency. The proposed approach ensures balancing of distribution micro-power systems taking into account the priority of consumers, minimizing electricity losses during network reconfiguration. The practical value of the approach is to determine irrational electricity flows taking into account the network capacity. Further research is related to modeling the balancing of micro-power systems taking into account stochastic regime data and the integration of decentralized sources.Recieved 2026-01-03Recieved 2026-01-30Accepted 2026-02-11
Keywords: micro-power system balancing; power shortage; priority consumers; optimal flow distribution; outage schedules